A hydrogen peroxide responsive prodrug of Keap1-Nrf2 inhibitor for improving oral absorption and selective activation in inflammatory conditions - Mengchen Lu; Xian Zhang; Jing Zhao; Qidong You; Zhengyu Jiang (Redox Biology, 2020)
Transcription factor Nuclear factor erythroid 2-related factor 2 (Nrf2) and its negative regulator, the E3 ligase adaptor Kelch-like ECH-associated protein 1 (Keap1), control the redox and metabolic homeostasis and oxidative stress. Inhibitors of Keap1-Nrf2 interaction are promising in oxidative stress related inflammatory diseases but now hit hurdles. By utilizing thiazolidinone moiety to shield the key carboxyl pharmacophore in Keap1-Nrf2 inhibitor, a hydrogen peroxide (H2O2)-responsive prodrug pro2 was developed. The prodrug modification improved the physicochemical properties and cell membrane permeability of the parent drug. Pro2 was stable and stayed inactive under various physiological conditions, while became active by stimulation of H2O2 or inflammation derived reactive oxygen species. Moreover, pro2 exhibited proper pharmacokinetic profile suitable for oral administration and enhanced anti-inflammatory efficiency in vivo. Thus, this novel prodrug approach may not only provide an important advance in the therapy of chronic inflammatory diseases with high level of H2O2, but also offer a fresh solution to improve the drug-like and selectivity issues of Keap1-Nrf2 inhibitors.